Patient safety : an engineering approach - Dhillon, B. S. (Balbir S.), 1947- (Boca Raton : Taylor & Francis, 2012)
'Each year a vast sum of money is spent on health care around the globe and patient safety has become a serious global public health issue. Filled with up-to-date information, this book demonstrates how to handle patient safety-related problems by using methods developed in the area of engineering. It contains a chapter on mathematical concepts and another chapter on introductory material on safety and human factors considered essential to understand materials presented in subsequent chapters. The author's presentation covers topics in such a manner that readers will require no previous knowledge to understand the concepts'--Provided by publisher.
Keywords: Safety Management -- methods; Equipment Safety -- methods; Models, Theoretical; Patient Care -- methods; Quality Assurance, Health Care -- methods